STUDY OF WORK LIFE BALANCE OF PNB EMPLOYEES - Choudhary, Savita; Kamlesh, (The journal of contemporary issues in business and government, 2022)
Work life and personal life are two sides of same coin. The entry or foreign and private banks havebrought radical changes in Banking Industry. Increasing work pressure, globalization, technological change etc.have created issues with both professional and personal life. Work deadlines are getting tighter and individuals fail to cope up with expected quality output. Work life balancehas become threat for employersand employees, both. The banking sector is one which is facing the problem of work life imbalance.Many atime people involve in reaching to the top work so hard that they miss out the on real pleasure of life. Theoutput of banking sector totally depends on human resources. Bank employees take pain full effort to caterto customer needs. This study aims at exploring the concept of work life balance and identifies the jobrelatedfactors thataffect theemployees’personal life.